A label for peer‐reviewed books. Issue 2 (21st December 2012) - Verleysen, Frederik T.; Engels, Tim C.E.
Abstract : The Publishers Association of Flanders, Belgium, has created a label for peer‐reviewed books: the Guaranteed Peer Reviewed Content (GPRC) label (www.gprc.be/en). We introduce the label and the logic behind it. A label for peer‐reviewed books encourages transparency in academic book publishing. It is especially relevant for the social sciences and humanities and in the context of performance‐based funding of university research.